International economics theory and policy - Krugman, Paul R.; Obstfeld, Maurice (Reading, Mass. Addison-Wesley, 2000)
"Krugman and Obstfeld provide a unified model of open-economy macroeconomics based upon an asset-market approach to exchange rate determination with a central role for expectations.
1. International economics: trade and money -- Part I. International trade theory -- 2. Labor productivity and comparative advantage: the Ricardian model -- 3. Specific factors and income distribution -- 4. Resources and trade: the Heckscher-Ohlin model -- 5. Standard trade model -- 6. Economies of scale, imperfect competition, and international trade -- 7. International factor movements -- Part II. International trade policy -- 8. Instruments of trade policy -- 9. Political economy of trade policy -- 10. Trade policy in developing countries -- 11. Strategic trade policies in advanced countries -- Part III. Exchange rates and open-economy macroeconomics -- 12. National income accounting and the balance of payments -- 13. Exchange rates and the foreign exchange market: an asset approach -- 14. Money, interest rates, and exchange rates -- 15. Price levels and the exchange rate in the long run -- 16. Output and the exchange rate in the short run -- 17. Fixed exchange rates and foreign exchange intervention -- Part IV. International macroeconomic policy -- 18. International monetary system, 1870-1973.
Keywords: International economic relations.".; International finance